2019
DOI: 10.12688/f1000research.18572.1
|View full text |Cite
|
Sign up to set email alerts
|

Thyroid hormonal changes among women with polycystic ovarian syndrome in Baghdad – a case-control study

Abstract: Background: Polycystic ovarian syndrome is a syndrome of ovarian dysfunction along with the cardinal features of hyperandrogenism and polycystic ovary morphology. The prevalence of polycystic ovaries on ultrasound is around quarter of all women but is not associated with the full syndrome. The study aimed to assess the status of thyroid disorders in polycystic ovarian syndrome (PCOS). Methods: This prospective hospital-based case-control study involved most outpatients aged 13–45 years who visited the Obstetri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 13 publications
1
2
0
Order By: Relevance
“…The BMI of the PCOS hypothyroid women shows significantly higher values when compared to control groups with (P = 0.013). These results are similar to the others results 7,12] Over weight and obesity are commonly observed in both PCOS and hypothyroidism, so there was a significant increase in the BMI in PCOS and hypothyroid groups 13 .…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The BMI of the PCOS hypothyroid women shows significantly higher values when compared to control groups with (P = 0.013). These results are similar to the others results 7,12] Over weight and obesity are commonly observed in both PCOS and hypothyroidism, so there was a significant increase in the BMI in PCOS and hypothyroid groups 13 .…”
Section: Discussionsupporting
confidence: 92%
“…The PCOS euthyroid group values were within the normal range but significantly higher than the control group where the p value was 0.001 and the PCOS hypothyroid group was very high compared to the control and the PCOS euthyroid groups. Many studies have been done to find out the association between the TSH and PCOS, but few studies reported an association between the control and PCOS groups as the TSH values were significantly higher in PCOS group compared to control groups 8,12,13 .…”
Section: Discussionmentioning
confidence: 99%
“…showed a significantly higher prevalence of autoimmune thyroiditis and goiter in PCOS patients than that in control subjects [26]. In another study, 20 (40%) of 50 patients with PCOS showed subclinical hyperthyroidism [27]. In a study, Michalakis et al reported prevalence of SCH was 23% among patients seeking treatment for infertility [28].…”
Section: Discussionmentioning
confidence: 91%
“…11 Moreover, most of the target population is teenagers and women of reproductive age, and they may be unavailable for transvaginal ultrasound evaluation because of their virginal status or obesity. 12 In addition to unclear diagnostic criteria, the presence of different phenotypes with PCOS further complicates the diagnosis. The technical advances in imaging have led to an artificial increase in PCOM resulting in confusion over its use as diagnostic criteria.…”
Section: Discussionmentioning
confidence: 99%